Voter Authentication System Using Fusion Process (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This voter identity verification system using fusion processauthenticates anindividualby means of three biometric features i.e; face, iris, palm with fusiontechnique.Thefeatures are obtained frompreprocessed images of face, iris, palm. The features of input image areequated withthe database image and a password is enteredto uphold validity. This contains mainly three stages i.e; pre-processing, DWTsegmentation and the fusion part.As soon as fusionmodule is done, the person is said to be either a valid voter or an invalid voter.